Fireproof low-voltage wire cable and preparation method thereof
By using nanomagnesium oxide and expanded graphite composite materials on the refractory layer of the refractory cable and forming a nanoceramic coating on its surface, the problem of insufficient thermal shock resistance of the refractory layer in high temperature environments is solved; nanocarbon tubes and nanotin dioxide particles are introduced into the outer sheath, and ultrasonic assisted microwave radiation technology is used to improve the weather resistance and mechanical properties of the outer sheath, ensuring the reliability and safety of the cable in high temperature and harsh environments.
Patent Information
- Application Number
- CN202510200939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The refractory layer of existing refractory cables has poor thermal shock resistance under high temperature environments and is prone to cracking or peeling. The outer sheath is susceptible to ultraviolet aging, ozone erosion and mechanical wear during long-term outdoor use.
A refractory layer is made of nanomagnesium oxide and expanded graphite composite materials, and a nanoceramic coating is formed on its surface, which is passed through chemical vapor deposition technology; nanocarbon tubes and nanotin dioxide particles are introduced into the outer sheath, and treated using ultrasonic assisted microwave radiation technology.
It significantly enhances the thermal shock resistance and high temperature stability of the refractory layer, extends the service life of the cable under extreme conditions, improves the weather resistance and mechanical properties of the outer sheath, and ensures the reliability and safety of the cable in high-temperature scenarios such as fires.
Smart Images

Figure CN119833220A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable preparation, in particular to a fire-resistant low-voltage electric wire and cable and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, the importance of building fire safety has become increasingly prominent. As an indispensable component of buildings, the fire resistance of wires and cables is directly related to the safety of personnel evacuation and equipment protection in the event of a fire. Patent announcement number CN118737555A discloses a fire-resistant building wire and cable and its preparation method. Although the cable is modified with magnesium hydroxide and a self-healing elastomer is introduced into the outer sheath, thereby greatly extending the service life of the wire and cable, it still has the following disadvantages: The fire-resistant layer of existing fire-resistant cables is usually wrapped and filled with mica tape, glass fiber and other materials. Although these materials have certain fire resistance, the thermal shock resistance of the fire-resistant layer is poor in high temperature environments. When the cable experiences rapid temperature changes in a fire, the fire-resistant layer is prone to cracking or peeling, resulting in a decrease in the fire resistance of the cable; The outer sheath of existing fire-resistant cables is usually made of materials such as polyethylene and ethylene-vinyl acetate copolymer. Although they have certain electrical insulation and weather resistance, the outer sheath is easily affected by ultraviolet aging, ozone erosion and mechanical wear during long-term outdoor use. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a fire-resistant low-voltage wire and cable and a preparation method thereof, which solves the problems raised in the background technology.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solutions: a fire-resistant low-voltage wire and cable and a preparation method thereof, the cable comprising, from inside to outside: The conductor layer, located in the center of the cable, is made of high-purity copper alloy; The insulating layer is tightly wrapped around the outside of the conductor layer and is made of micro-nano composite polyimide material; The fire-resistant layer is tightly wrapped around the outside of the insulating layer and is made of a composite material of nano magnesium oxide and expanded graphite; A waterproof layer, tightly wrapped around the outside of the fire-resistant layer, made of nano-diatomaceous earth and polyurethane composite material; The anti-corrosion layer is tightly wrapped around the outside of the waterproof layer and is made of a composite material of nano zinc powder and epoxy resin; A shielding layer, tightly wrapped around the anti-corrosion layer, made of a composite material of nano silver particles and copper fibers; The outer sheath is tightly wrapped around the outside of the shielding layer and is made of a composite material of nano carbon tubes and polyvinyl chloride.
[0005] Preferably, S01. Conductor preparation: select a copper alloy with a purity of ≥99.9% as the conductor material; uniformly disperse a nano-scale graphene composite material with a particle size of ≤100nm in the copper alloy at a mass ratio of 1% to 3%; use high-energy ball milling to mix the graphene and the copper alloy to ensure that the graphene is evenly distributed; place the treated copper alloy conductor in a low-temperature plasma treatment device, set the power to 500~1000W, and the treatment time is 10~20 minutes; form a nano-scale porous microstructure on the surface of the conductor to enhance the adhesion and corrosion resistance of the conductor; S02. Preparation of insulating layer: Nano-alumina with a particle size of ≤50nm and micron-sized mica particles with a particle size of ≤10μm are uniformly dispersed in a polyimide matrix at a mass ratio of 1:2; nano-titanium dioxide with a particle size of ≤30nm is added as an auxiliary reinforcing material at a mass ratio of 0.5%; the mixed material is dispersed by ultrasonic wave with an ultrasonic power of 300~500W and a treatment time of 30~60 minutes; the mixed material is made into an insulating layer of nanofiber structure by electrospinning with a fiber diameter of 100~300nm; the prepared insulating layer is uniformly wrapped on the outside of the conductor layer with a thickness of 0.5~1mm; S03. Preparation of refractory layer: nano magnesium oxide with a particle size of ≤50nm and expanded graphite with a particle size of ≤100μm are mixed in a mass ratio of 1:1; nano silicon carbide particles (particle size ≤30nm) are added in a mass ratio of 0.5%; a nano ceramic coating is formed on the surface of the refractory layer using chemical vapor deposition (CVD); the deposition temperature is 800~1000℃, the deposition time is 30~60 minutes, and the coating thickness is 50~100nm; the prepared refractory layer is evenly wrapped on the outside of the insulating layer with a thickness of 1~2mm; S04. Preparation of waterproof layer: evenly mix nano-diatomite with a particle size of ≤50nm and polyurethane in a mass ratio of 1:5; use in-situ polymerization technology to evenly disperse the nano-diatomite in the polyurethane matrix; ensure the uniformity of the material through a nano-dispersion method; evenly wrap the prepared waterproof layer on the outside of the fire-resistant layer with a thickness of 0.5~1mm; S05. Preparation of anti-corrosion layer: Mix nano zinc powder with a particle size of ≤50nm and epoxy resin in a mass ratio of 1:3; add nano zinc oxide particles with a particle size of ≤30nm, with a mass ratio of 0.5%; modify the anti-corrosion layer by plasma surface treatment, with a power of 300~500W and a treatment time of 10~20 minutes; form a nano self-healing coating on the surface of the anti-corrosion layer with a thickness of 50~100nm; evenly wrap the prepared anti-corrosion layer on the outside of the waterproof layer with a thickness of 0.5~1mm; S06. Preparation of shielding layer: Mix nanosilver particles with a particle size of ≤50nm and copper fibers with a diameter of ≤10μm; add nano-graphene with a mass ratio of 0.5%; use electromagnetic induction heating technology to treat the mixed material at a temperature of 300~500℃ for 10~20 minutes; ensure that the nanosilver particles are evenly distributed on the surface of the copper fibers; evenly wrap the prepared shielding layer on the outside of the anti-corrosion layer with a thickness of 0.5~1mm; S07. Preparation of outer sheath: Mix carbon nanotubes with a diameter of ≤20nm and polyvinyl chloride; add nano-alumina particles with a particle size of ≤30nm; use microwave-assisted extrusion technology to process the mixed material, with a microwave power of 500~1000W and an extrusion temperature of 150~200℃; ensure that the carbon nanotubes are evenly distributed in the polyvinyl chloride matrix; evenly wrap the prepared outer sheath on the outside of the shielding layer with a thickness of 1~2mm.
[0006] Preferably, in step S01, during the low-temperature plasma treatment, the pore size of the nanoscale porous structure formed on the surface of the conductor is 10~50nm, and the porosity is 5%~15%, so as to further enhance the adhesion and corrosion resistance of the conductor; the nano-composite enhancement treatment also includes adding nano-scale boron carbide particles with a particle size of ≤50nm to the copper alloy, with a mass ratio of 0.1%~0.5%.
[0007] Preferably, in step S02, in the nanofiber structure of the insulating layer, the fiber diameter is 150-250 nm, and the interlacing angle between the fibers is 30°-60°, so as to improve the mechanical strength and fire resistance of the insulating layer; in addition, the insulating layer is surface treated by photocuring technology, the curing energy is 800-1000 mJ / cm² in the UV band, and the line speed is 90-100 m / min.
[0008] Preferably, in step S03, the nano-ceramic coating is formed by mixing nano-magnesium oxide with a particle size of ≤50nm and expanded graphite with a particle size of ≤100μm in a mass ratio of 1:1, and nano-scale boron nitride particles with a particle size of ≤30nm are added in a mass ratio of 0.1%~0.5%; during the CVD deposition process, a dynamic gradient heating process is introduced: first, the conductor is induction heated and preheated to 87-93°C, and then the temperature is gradually increased to 800-1000°C during the deposition process to achieve uniform deposition of the coating and enhance adhesion. The dynamic gradient heating process controls the temperature change in stages so that the coating adapts to thermal stress changes during the deposition process.
[0009] Preferably, in step S04, during the preparation of the waterproof layer, nano diatomaceous earth (particle size ≤ 50 nm) and polyurethane are mixed in a mass ratio of 1:5, and nano-scale cerium dioxide particles with a particle size of ≤ 30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is treated by photocatalytic grafting technology, and the photocatalytic activity on the surface of the nano cerium dioxide particles is activated by ultraviolet light irradiation (wavelength 254 to 365 nm), so that it undergoes a grafting reaction with the polyurethane matrix to form a composite coating with anti-ultraviolet function. After the photocatalytic grafting treatment, the composite material is evenly sprayed on the surface of the refractory layer by high-pressure spraying technology, with a spraying amount of 100-110 g / m² and a spraying pressure of 0.3-0.5 MPa to ensure the uniformity and adhesion of the coating.
[0010] Preferably, in step S05, during the preparation of the anti-corrosion layer, the epoxy resin matrix is pretreated by plasma surface treatment technology to introduce highly active functional groups (such as hydroxyl groups and carboxyl groups) to enhance the dispersibility of the nanoparticles and the adhesion of the coating. Nano zinc powder (particle size ≤ 50 nm) and nano-scale manganese dioxide particles (particle size ≤ 30 nm) are added to the epoxy resin matrix after plasma treatment in a mass ratio of 1:3 and 0.2% to 0.5%, respectively, and the nano-composite material is uniformly dispersed in the epoxy resin by an in-situ polymerization process; the in-situ polymerization process ensures that the nanoparticles are tightly bonded to the epoxy resin matrix by stirring at 60-80°C for 30-60 minutes and then curing at 120-150°C for 2-3 hours.
[0011] Preferably, in step S06, during the preparation of the shielding layer, the nano-silver particles and the copper fibers are mixed in a mass ratio of 1:5, and nano-scale tungsten carbide particles with a particle size of ≤30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is pretreated by low-temperature plasma surface treatment technology, the power is set to 300 to 500 W, and the treatment time is 10 to 20 minutes to introduce highly active functional groups, enhance the dispersibility of the nano-particles and the adhesion of the coating, and in the composite material after plasma treatment, the electromagnetic induction heating technology is used to treat it at 300 to 500°C for 10 to 20 minutes to ensure that the nano-silver particles and the nano-tungsten carbide particles are evenly distributed on the surface of the copper fiber.
[0012] Preferably, in step S07, during the preparation of the outer sheath, carbon nanotubes (diameter ≤ 20 nm) and polyvinyl chloride are mixed in a mass ratio of 1:10, and nano-scale tin dioxide particles with a particle size of ≤ 30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is treated with ultrasound-assisted microwave radiation technology, wherein the ultrasound power is 300 to 500 W and the treatment time is 10 to 20 minutes; the microwave radiation power is 500 to 1000 W and the radiation time is 5 to 10 minutes. During the treatment process, the dispersion of carbon nanotubes and nano-tin dioxide particles in the polyvinyl chloride matrix is enhanced by ultrasound-assisted technology, and microwave radiation technology is used to promote uniform mixing of the composite material and optimization of physical properties.
[0013] Preferably, in step S06, during the preparation of the shielding layer, a layer of nano-scale conductive coating is formed on the surface of the shielding layer by plasma enhanced chemical vapor deposition (PECVD) technology; the coating is composed of nano silver particles and graphene composite materials, and is deposited under low temperature conditions by plasma enhanced technology, with a thickness of 50-100nm; the electromagnetic shielding performance of the shielding layer is improved, and its corrosion resistance and wear resistance are enhanced; the specific process steps are as follows: Preparation of coating material: Nano-silver particles with a particle size of ≤50 nm and graphene with an interlayer spacing of ≤0.4 nm are mixed in a mass ratio of 1:2 to form a composite material; Plasma enhanced deposition: PECVD technology is used on the surface of the shielding layer to excite the deposition gas (containing silver precursor and graphene dispersion) through radio frequency plasma (frequency 13.56MHz) and deposit at a low temperature of 200-300℃; Deposition parameter control: deposition time is 30-60 minutes, deposition pressure is 0.1-0.5Pa, and deposition power is 50-100W to ensure uniformity and adhesion of the coating; Coating performance optimization: By adjusting the ratio of nanosilver particles and graphene, as well as deposition parameters, the electromagnetic shielding effectiveness (EMISE) of the coating can reach 40-50dB in the X-band (8.2-12.4GHz).
[0014] The present invention provides a fire-resistant low-voltage wire and cable and a preparation method thereof. The invention has the following beneficial effects: (1) A fire-resistant low-voltage wire and cable and its preparation method, by using chemical vapor deposition (CVD) technology to form a nano-ceramic coating on the surface of the fire-resistant layer and introducing nano-sized boron nitride particles, this scheme significantly enhances the thermal shock resistance and high-temperature stability of the fire-resistant layer. CVD technology can achieve high-quality nano-ceramic coating deposition at a lower temperature, ensuring the close bonding of the coating and the substrate, while the addition of nano-boron nitride particles further improves the thermal conductivity and thermal shock resistance of the coating; this improvement not only enables the fire-resistant layer to withstand rapid temperature changes without cracking in a high-temperature environment, but also effectively extends the service life of the cable under extreme conditions, ensuring the reliability and safety of the cable in high-temperature scenarios such as fire; in addition, the improvement of the uniformity and adhesion of the nano-ceramic coating also further enhances the overall performance of the fire-resistant layer, giving it a significant performance advantage in the field of fire-resistant cables.
[0015] (2) A fire-resistant low-voltage wire and cable and a preparation method thereof, wherein nano-carbon tubes and nano-tin dioxide particles are introduced into the outer sheath, and combined with ultrasound-assisted microwave radiation technology, this scheme greatly improves the weather resistance and mechanical properties of the outer sheath; the addition of nano-carbon tubes significantly enhances the mechanical strength and conductivity of the outer sheath, while the nano-tin dioxide particles give the outer sheath excellent weather resistance and UV resistance; the application of ultrasound-assisted microwave radiation technology further optimizes the dispersion of nano-particles in the matrix, ensuring that the outer sheath can resist UV aging, ozone erosion and mechanical wear during long-term outdoor use; this improvement not only enables the outer sheath to maintain good physical properties in harsh environments, but also significantly extends the service life of the cable, reduces maintenance costs, and improves the reliability and economy of the cable in outdoor applications.
[0016] (3) A fire-resistant low-voltage wire and cable and its preparation method. This solution significantly simplifies the preparation process of the fire-resistant layer and the outer sheath through a dynamic gradient heating process and ultrasound-assisted microwave radiation technology, and improves the uniformity and adhesion of the coating. The dynamic gradient heating process controls the temperature change in stages during the preparation of the fire-resistant layer, so that the coating adapts to the thermal stress change during the deposition process, thereby significantly improving the thermal shock resistance and adhesion of the coating. The ultrasound-assisted microwave radiation technology enhances the dispersion of nanoparticles and the uniformity of the coating through high-frequency vibration and microwave radiation during the preparation of the outer sheath, and further optimizes the performance of the outer sheath. This process improvement not only improves production efficiency and reduces production costs, but also ensures the high quality and high performance of each layer of the cable, so that it has significant process advantages and economic value in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the overall structure of the present invention; Figure 2 It is a schematic diagram of the process of the present invention.
[0018] In the figure, 1. conductor layer; 2. insulation layer; 3. fire-resistant layer; 4. waterproof layer; 5. anti-corrosion layer; 6. shielding layer; 7. outer sheath. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: A method for preparing a fire-resistant low-voltage wire and cable, the specific steps are as follows: Conductor preparation (S01): Use copper alloy with purity ≥99.9% as conductor material; The nano-graphene composite material with a particle size of ≤100 nm is uniformly dispersed in the copper alloy at a mass ratio of 1%; Graphene is mixed with copper alloy using high-energy ball milling technology to ensure that the graphene is evenly distributed; The treated copper alloy conductor is placed in a low-temperature plasma treatment device, the power is set to 500 W, and the treatment time is 10 minutes; Form a nanoscale porous microstructure on the conductor surface with a pore size of 10 nm and a porosity of 5%, which enhances the adhesion and corrosion resistance of the conductor; Insulation layer preparation (S02): Nano-alumina particles with a particle size of ≤50 nm and micro-mica particles with a particle size of ≤10 μm are uniformly dispersed in a polyimide matrix in a mass ratio of 1:2; Add nano-sized titanium dioxide with a particle size of ≤30 nm, with a mass ratio of 0.5%; The mixed material was treated using ultrasonic dispersion technology, with an ultrasonic power of 300 W and a treatment time of 30 min; The mixed material was made into an insulating layer of nanofiber structure using electrospinning technology. The fiber diameter was 150 nm and the interweaving angle between the fibers was 30°. The prepared insulating layer is evenly wrapped around the conductor layer with a thickness of 0.5 mm; Refractory layer preparation (S03): Nano magnesium oxide with a particle size of ≤50 nm and expanded graphite with a particle size of ≤100 μm are mixed in a mass ratio of 1:1; Add nano-sized boron nitride particles with a particle size of ≤30 nm, with a mass ratio of 0.1%; A nano-scale ceramic coating was formed on the surface of the refractory layer using chemical vapor deposition (CVD) technology, with a deposition temperature of 800°C, a deposition time of 30 minutes, and a coating thickness of 50 nm. Introducing a dynamic gradient heating process: first, the conductor is inductively heated to 87°C, and then the temperature is gradually increased to 800°C during the deposition process; Waterproof layer preparation (S04): Nano-diatomaceous earth with a particle size of ≤50 nm and polyurethane are uniformly mixed in a mass ratio of 1:5; Add nano-sized cerium dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.2%; The composite material was treated by photocatalytic grafting technology, with the UV irradiation wavelength of 254 nm and the treatment time of 30 minutes; The composite material is evenly sprayed on the surface of the refractory layer through high-pressure spraying technology, with a spraying amount of 100 g / m² and a spraying pressure of 0.3 MPa to ensure the uniformity and adhesion of the coating; Preparation of anti-corrosion layer (S05): Nano zinc powder with a particle size of ≤50 nm and epoxy resin are mixed in a mass ratio of 1:3; Add nano-sized manganese dioxide particles with a particle size of ≤30 nm, with a mass ratio of 0.2%; The anti-corrosion layer was modified using plasma surface treatment technology, with a power of 300 W and a treatment time of 10 minutes; A nanoscale self-repairing coating with a thickness of 50 nm is formed on the surface of the anti-corrosion layer; The prepared anti-corrosion layer is evenly wrapped on the outside of the waterproof layer with a thickness of 0.5 mm; Shielding layer preparation (S06): Nanosilver particles with a particle size of ≤50 nm and copper fibers with a diameter of ≤10 μm are mixed in a mass ratio of 1:5; Add nano-sized tungsten carbide particles with a particle size of ≤30 nm, with a mass ratio of 0.2%; The composite material was pretreated using low-temperature plasma surface treatment technology with a power of 300 W and a treatment time of 10 minutes; Electromagnetic induction heating technology was used to treat the copper fibers at 300°C for 10 minutes to ensure that the nano-silver particles and nano-tungsten carbide particles were evenly distributed on the surface of the copper fibers. The prepared shielding layer is evenly wrapped around the anti-corrosion layer with a thickness of 0.5 mm; Outer sheath preparation (S07): Carbon nanotubes with a diameter of ≤20 nm and polyvinyl chloride are mixed in a mass ratio of 1:10; Add nano-sized tin dioxide particles with a particle size of ≤30 nm, with a mass ratio of 0.2%; The composite material was treated by ultrasound-assisted microwave radiation technology, with an ultrasound power of 300 W and a treatment time of 10 minutes; the microwave radiation power was 500 W and the radiation time was 5 minutes; Wrap the prepared outer sheath evenly around the shielding layer with a thickness of 1 mm.
[0021] Example 2 A method for preparing a fire-resistant low-voltage wire and cable, the specific steps are as follows: Conductor preparation (S01): Use copper alloy with purity ≥99.9% as conductor material; The nano-graphene composite material with a particle size of ≤100 nm is uniformly dispersed in the copper alloy at a mass ratio of 2%; Graphene is mixed with copper alloy using high-energy ball milling technology to ensure that the graphene is evenly distributed; The treated copper alloy conductor is placed in a low-temperature plasma treatment device, the power is set to 750 W, and the treatment time is 15 minutes; Forming a nanoscale porous microstructure on the conductor surface with a pore size of 30 nm and a porosity of 10%, enhancing the conductor's adhesion and corrosion resistance; Insulation layer preparation (S02): Nano-alumina particles with a particle size of ≤50 nm and micro-mica particles with a particle size of ≤10 μm are uniformly dispersed in a polyimide matrix in a mass ratio of 1:2; Add nano-sized titanium dioxide with a particle size of ≤30 nm, with a mass ratio of 0.5%; The mixed material was treated using ultrasonic dispersion technology, with an ultrasonic power of 400 W and a treatment time of 45 min; The mixed material was made into an insulating layer of nanofiber structure using electrospinning technology. The fiber diameter was 200 nm and the interweaving angle between the fibers was 45°. The prepared insulating layer is evenly wrapped around the conductor layer with a thickness of 0.7 mm; Refractory layer preparation (S03): Nano magnesium oxide with a particle size of ≤50 nm and expanded graphite with a particle size of ≤100 μm are mixed in a mass ratio of 1:1; Add nano-sized boron nitride particles with a particle size of ≤30 nm, with a mass ratio of 0.3%; A nano-scale ceramic coating was formed on the surface of the refractory layer using chemical vapor deposition (CVD) technology. The deposition temperature was 900°C, the deposition time was 45 minutes, and the coating thickness was 75 nm. Introducing a dynamic gradient heating process: first, the conductor is inductively heated to 90°C, and then the temperature is gradually increased to 900°C during the deposition process; Waterproof layer preparation (S04): Nano-diatomaceous earth with a particle size of ≤50 nm and polyurethane are uniformly mixed in a mass ratio of 1:5; Add nano-sized cerium dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.3%; The composite material was treated by photocatalytic grafting technology, with the UV irradiation wavelength of 300 nm and the treatment time of 45 minutes; The composite material is evenly sprayed on the surface of the refractory layer through high-pressure spraying technology, with a spraying amount of 105 g / m² and a spraying pressure of 0.4 MPa to ensure the uniformity and adhesion of the coating; Preparation of anti-corrosion layer (S05): Nano zinc powder with a particle size of ≤50 nm and epoxy resin are mixed in a mass ratio of 1:3; Add nano-sized manganese dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.3%; The anti-corrosion layer was modified using plasma surface treatment technology, with a power of 400 W and a treatment time of 15 minutes; A nanoscale self-repairing coating with a thickness of 75 nm is formed on the surface of the anti-corrosion layer; The prepared anti-corrosion layer is evenly wrapped around the outside of the waterproof layer with a thickness of 0.7 mm; Shielding layer preparation (S06): Nanosilver particles with a particle size of ≤50 nm and copper fibers with a diameter of ≤10 μm are mixed in a mass ratio of 1:5; Add nano-sized tungsten carbide particles with a particle size of ≤30 nm, with a mass ratio of 0.3%; The composite material was pretreated using low-temperature plasma surface treatment technology with a power of 400 W and a treatment time of 15 minutes; Electromagnetic induction heating technology was used to treat the copper fibers at 350°C for 15 minutes to ensure that the nano-silver particles and nano-tungsten carbide particles were evenly distributed on the surface of the copper fibers. The prepared shielding layer is evenly wrapped around the anti-corrosion layer with a thickness of 0.7 mm; Outer sheath preparation (S07): Carbon nanotubes with a diameter of ≤20 nm and polyvinyl chloride are mixed in a mass ratio of 1:10; Add nano-sized tin dioxide particles with a particle size of ≤30 nm, with a mass ratio of 0.3%; The composite material was treated by ultrasound-assisted microwave radiation technology, with an ultrasound power of 400 W and a treatment time of 15 minutes; the microwave radiation power was 750 W and the radiation time was 7.5 minutes; The prepared outer sheath is evenly wrapped around the outside of the shielding layer with a thickness of 1.5 mm.
[0022] Example 3 A method for preparing a fire-resistant low-voltage wire and cable, the specific steps are as follows: Conductor preparation (S01): Use copper alloy with purity ≥99.9% as conductor material; The nano-graphene composite material with a particle size of ≤100 nm is uniformly dispersed in the copper alloy at a mass ratio of 3%; Graphene is mixed with copper alloy using high-energy ball milling technology to ensure that the graphene is evenly distributed; The treated copper alloy conductor is placed in a low-temperature plasma treatment device, the power is set to 1000 W, and the treatment time is 20 minutes; Forming a nanoscale porous microstructure on the conductor surface with a pore size of 50 nm and a porosity of 15%, enhancing the conductor's adhesion and corrosion resistance; Insulation layer preparation (S02): Nano-alumina particles with a particle size of ≤50 nm and micro-mica particles with a particle size of ≤10 μm are uniformly dispersed in a polyimide matrix in a mass ratio of 1:2; Add nano-sized titanium dioxide with a particle size of ≤30 nm, with a mass ratio of 0.5%; The mixed material was treated using ultrasonic dispersion technology, with an ultrasonic power of 500 W and a treatment time of 60 min; The mixed material was made into an insulating layer of nanofiber structure using electrospinning technology. The fiber diameter was 250 nm and the interweaving angle between the fibers was 60°. The prepared insulating layer is evenly wrapped around the conductor layer with a thickness of 1 mm; Refractory layer preparation (S03): Nano magnesium oxide with a particle size of ≤50 nm and expanded graphite with a particle size of ≤100 μm are mixed in a mass ratio of 1:1; Add nano-sized boron nitride particles with a particle size of ≤30 nm, with a mass ratio of 0.5%; A nano-scale ceramic coating is formed on the surface of the refractory layer using chemical vapor deposition (CVD) technology, with a deposition temperature of 1000°C, a deposition time of 60 minutes, and a coating thickness of 100 nm; Introducing a dynamic gradient heating process: first, the conductor is inductively heated to 93°C, and then the temperature is gradually increased to 1000°C during the deposition process; Waterproof layer preparation (S04): Nano-diatomaceous earth with a particle size of ≤50 nm and polyurethane are uniformly mixed in a mass ratio of 1:5; Add nano-sized cerium dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.5%; The composite material was treated by photocatalytic grafting technology, with the UV irradiation wavelength of 365 nm and the treatment time of 60 minutes; The composite material is evenly sprayed on the surface of the refractory layer through high-pressure spraying technology, with a spraying amount of 110 g / m² and a spraying pressure of 0.5 MPa to ensure the uniformity and adhesion of the coating; Preparation of anti-corrosion layer (S05): Nano zinc powder with a particle size of ≤50 nm and epoxy resin are mixed in a mass ratio of 1:3; Add nano-sized manganese dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.5%; The anti-corrosion layer was modified using plasma surface treatment technology, with a power of 500 W and a treatment time of 20 minutes; A nanoscale self-repairing coating with a thickness of 100 nm is formed on the surface of the anti-corrosion layer; The prepared anti-corrosion layer is evenly wrapped around the outside of the waterproof layer with a thickness of 1 mm; Shielding layer preparation (S06): Nanosilver particles with a particle size of ≤50 nm and copper fibers with a diameter of ≤10 μm are mixed in a mass ratio of 1:5; Add nano-sized tungsten carbide particles with a particle size of ≤30 nm, with a mass ratio of 0.5%; The composite material was pretreated using low-temperature plasma surface treatment technology with a power of 500 W and a treatment time of 20 minutes; Electromagnetic induction heating technology was used to treat the copper fibers at 500°C for 20 minutes to ensure that the nano-silver particles and nano-tungsten carbide particles were evenly distributed on the surface of the copper fibers. The prepared shielding layer is evenly wrapped around the anti-corrosion layer with a thickness of 1 mm; Outer sheath preparation (S07): Carbon nanotubes with a diameter of ≤20 nm and polyvinyl chloride are mixed in a mass ratio of 1:10; Add nano-sized tin dioxide particles with a particle size of ≤30 nm at a mass ratio of 0.5%; The composite material was treated by ultrasound-assisted microwave radiation technology, with an ultrasound power of 500 W and a treatment time of 20 minutes; the microwave radiation power was 1000 W and the radiation time was 10 minutes; Wrap the prepared outer sheath evenly around the shielding layer with a thickness of 2 mm.
[0023] Comparative Example 1 A method for preparing a fire-resistant low-voltage wire and cable. Compared with Example 1, only in the preparation of the fire-resistant layer (S03), no nano-sized boron nitride particles are added, and the other steps and parameters remain the same.
[0024] Comparative Example 2 A method for preparing a fire-resistant low-voltage wire and cable, compared with Example 1, only in the preparation of the outer sheath (S07), the composite material is not treated with ultrasound-assisted microwave radiation technology, but microwave-assisted extrusion is directly performed, and the other steps and parameters remain the same.
[0025] The fire-resistant low-voltage wires and cables prepared in the above embodiments and comparative examples were subjected to performance tests, and the test items included: Fire resistance performance: Fire resistance test is carried out in accordance with GB / T 18380 standard; Thermal shock resistance: Rapidly cool from 800°C to room temperature, repeat 10 times, and observe whether the refractory layer cracks or peels off; Weather resistance: Expose the outer sheath sample in a UV aging box with a wavelength of 340 nm for 1000 hours to observe whether cracks or powdering appear on the surface; project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Fire resistance excellent excellent excellent good good Thermal shock resistance No cracking No cracking No cracking Cracking No cracking Weather resistance No cracks No cracks No cracks No cracks Powdering Tensile strength (MPa) 35 38 40 30 28 Elongation at break (%) 500 550 600 400 350 By comparing the test results of the embodiments and the comparative examples, it can be seen that: The addition of nano-sized boron nitride particles in the refractory layer (Examples 1, 2, and 3) significantly improved the thermal shock resistance of the refractory layer, while in Comparative Example 1, the particles were not added and the refractory layer cracked during rapid cooling; The outer sheath adopts ultrasound-assisted microwave radiation technology (Examples 1, 2, and 3) to significantly improve the weather resistance and mechanical properties of the outer sheath, while the comparative example 2 does not adopt this technology, and the outer sheath becomes powdery under ultraviolet irradiation, and the tensile strength and elongation at break are low; Under the optimized parameters of each layer, Example 3 has the best comprehensive performance, and its fire resistance, thermal shock resistance, weather resistance and mechanical properties are all better than those of other examples.
[0026] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0027] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A fire-resistant low-voltage wire and cable and a method for preparing the same, characterized in that: The cable includes, from inside to outside: The conductor layer (1) is located at the center of the cable and is made of a high-purity copper alloy; The insulating layer (2) is tightly wrapped around the outside of the conductor layer (1) and is made of a micro-nano composite polyimide material; A fire-resistant layer (3), tightly wrapped around the outside of the insulating layer (2), and made of a composite material of nano-magnesium oxide and expanded graphite; A waterproof layer (4), tightly wrapped around the outside of the fire-resistant layer (3), and made of a composite material of nano-diatomaceous earth and polyurethane; The anti-corrosion layer (5) is tightly wrapped around the outside of the waterproof layer (4) and is made of a composite material of nano zinc powder and epoxy resin; A shielding layer (6), tightly wrapped around the outside of the anti-corrosion layer (5), and made of a composite material of nano silver particles and copper fibers; The outer sheath (7) is tightly wrapped around the outside of the shielding layer (6) and is made of a composite material of nano carbon tubes and polyvinyl chloride.
2. A method for preparing a fire-resistant low-voltage wire and cable according to claim 1, characterized in that: S01. Conductor preparation: select copper alloy with purity ≥99.9% as conductor material; evenly disperse nano-graphene composite material with particle size ≤100nm in copper alloy at a mass ratio of 1%~3%; use high-energy ball milling to mix graphene and copper alloy to ensure uniform distribution of graphene; place the treated copper alloy conductor in low-temperature plasma treatment equipment, set the power to 500~1000W, and the treatment time is 10~20 minutes; form a nano-scale porous microstructure on the surface of the conductor to enhance the adhesion and corrosion resistance of the conductor; S02. Preparation of insulating layer (2): Nano-alumina particles with a particle size of ≤50 nm and micron-sized mica particles with a particle size of ≤10 μm are uniformly dispersed in a polyimide matrix at a mass ratio of 1:2; nano-titanium dioxide particles with a particle size of ≤30 nm are added as an auxiliary reinforcing material at a mass ratio of 0.5%; the mixed material is dispersed by ultrasonic wave with an ultrasonic power of 300-500 W and a treatment time of 30-60 minutes; the mixed material is made into an insulating layer (2) of nanofiber structure by electrospinning with a fiber diameter of 100-300 nm; the prepared insulating layer (2) is uniformly wrapped on the outside of the conductor layer (1) with a thickness of 0.5-1 mm; S03. Preparation of the refractory layer (3): nano-magnesium oxide with a particle size of ≤50 nm and expanded graphite with a particle size of ≤100 μm are mixed in a mass ratio of 1:1; nano-sized silicon carbide particles (particle size ≤30 nm) are added in a mass ratio of 0.5%; and a nano-sized ceramic coating is formed on the surface of the refractory layer (3) by chemical vapor deposition (CVD); The deposition temperature is 800-1000°C, the deposition time is 30-60 minutes, and the coating thickness is 50-100 nm; the prepared refractory layer (3) is evenly wrapped around the outside of the insulating layer (2) with a thickness of 1-2 mm; S04. Preparation of waterproof layer (4): uniformly mix nano-diatomite with a particle size of ≤50 nm and polyurethane in a mass ratio of 1:5; uniformly disperse the nano-diatomite in the polyurethane matrix using an in-situ polymerization technique; ensure the uniformity of the material by a nano-dispersion method; uniformly wrap the prepared waterproof layer (4) on the outside of the fire-resistant layer (3) to a thickness of 0.5 to 1 mm; S05. Preparation of the anti-corrosion layer (5): using nano zinc powder with a particle size of ≤50 nm and epoxy resin in a mass ratio of 1:3; adding nano zinc oxide particles with a particle size of ≤30 nm in a mass ratio of 0.5%; using plasma surface treatment to modify the anti-corrosion layer (5) at a power of 300-500 W and a treatment time of 10-20 minutes; forming a nano self-healing coating on the surface of the anti-corrosion layer (5) with a thickness of 50-100 nm; and uniformly wrapping the prepared anti-corrosion layer (5) on the outside of the waterproof layer (4) with a thickness of 0.5-1 mm; S06. Preparation of shielding layer (6): Mixing nanosilver particles with a particle size of ≤50 nm and copper fibers with a diameter of ≤10 μm; adding nanographene with a mass ratio of 0.5%; using electromagnetic induction heating technology to treat the mixed material at a temperature of 300-500°C for 10-20 minutes; ensuring that the nanosilver particles are evenly distributed on the surface of the copper fibers; uniformly wrapping the prepared shielding layer (6) on the outside of the anti-corrosion layer (5) with a thickness of 0.5-1 mm; S07. Preparation of outer sheath (7): Mix carbon nanotubes with a diameter of ≤20 nm and polyvinyl chloride; add nano-alumina particles with a particle size of ≤30 nm; use microwave-assisted extrusion technology to process the mixed material, with a microwave power of 500~1000W and an extrusion temperature of 150~200℃; ensure that the carbon nanotubes are evenly distributed in the polyvinyl chloride matrix; and evenly wrap the prepared outer sheath (7) on the outside of the shielding layer (6) with a thickness of 1~2 mm.
3. A method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S01, during the low-temperature plasma treatment, the nanoscale porous structure formed on the surface of the conductor has a pore size of 10-50 nm and a porosity of 5%-15%, so as to further enhance the adhesion and corrosion resistance of the conductor; the nano-composite enhancement treatment also includes adding nano-scale boron carbide particles with a particle size of ≤50 nm to the copper alloy, with a mass ratio of 0.1%-0.5%.
4. A method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S02, in the nanofiber structure of the insulating layer (2), the fiber diameter is 150-250 nm, and the interlacing angle between the fibers is 30°-60°, so as to improve the mechanical strength and fire resistance of the insulating layer (2); in addition, the insulating layer (2) is surface treated by photocuring technology, the curing energy is 800-1000 mJ / cm² under the UV band, and the line speed is 90-100 m / min.
5. The method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S03, the nano-ceramic coating is formed by mixing nano-magnesium oxide with a particle size of ≤50nm and expanded graphite with a particle size of ≤100μm in a mass ratio of 1:1, and nano-scale boron nitride particles with a particle size of ≤30nm are added in a mass ratio of 0.1%~0.5%; during the CVD deposition process, a dynamic gradient heating process is introduced: first, the conductor is induction heated and preheated to 87-93°C, and then the temperature is gradually increased to 800-1000°C during the deposition process to achieve uniform deposition of the coating and enhance adhesion. The dynamic gradient heating process controls the temperature change in stages so that the coating can adapt to thermal stress changes during the deposition process.
6. A method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S04, during the preparation of the waterproof layer (4), nano-diatomaceous earth (particle size ≤ 50 nm) and polyurethane are mixed in a mass ratio of 1:5, and nano-scale cerium dioxide particles with a particle size ≤ 30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is treated by photocatalytic grafting technology. The photocatalytic activity on the surface of the nano-cerium dioxide particles is activated by ultraviolet light irradiation (wavelength 254 to 365 nm), so that the nano-cerium dioxide particles undergo a grafting reaction with the polyurethane matrix to form a composite coating with anti-ultraviolet function. After the photocatalytic grafting treatment, the composite material is evenly sprayed on the surface of the fire-resistant layer (3) by high-pressure spraying technology. The spraying amount is 100-110 g / m² and the spraying pressure is 0.3-0.5 MPa to ensure the uniformity and adhesion of the coating.
7. The method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S05, during the preparation of the anti-corrosion layer (5), the epoxy resin matrix is pretreated by plasma surface treatment technology to introduce highly active functional groups (such as hydroxyl groups and carboxyl groups) to enhance the dispersibility of the nanoparticles and the adhesion of the coating. Nano zinc powder (particle size ≤ 50 nm) and nano manganese dioxide particles (particle size ≤ 30 nm) are added to the epoxy resin matrix after plasma treatment in a mass ratio of 1:3 and 0.2% to 0.5%, respectively. The nano composite material is uniformly dispersed in the epoxy resin by an in-situ polymerization process. The in-situ polymerization process ensures that the nanoparticles are tightly bonded to the epoxy resin matrix by stirring at 60-80° C. for 30-60 minutes and then curing at 120-150° C. for 2-3 hours.
8. The method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S06, during the preparation of the shielding layer (6), the nano silver particles and the copper fibers are mixed in a mass ratio of 1:5, and nano tungsten carbide particles with a particle size of ≤30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is pretreated by a low temperature plasma surface treatment technology, with a power setting of 300 to 500 W and a treatment time of 10 to 20 minutes, so as to introduce highly active functional groups and enhance the dispersibility of the nano particles and the adhesion of the coating. In the composite material after the plasma treatment, the electromagnetic induction heating technology is used to treat it at 300 to 500° C. for 10 to 20 minutes to ensure that the nano silver particles and the nano tungsten carbide particles are evenly distributed on the surface of the copper fibers.
9. The method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S07, during the preparation of the outer sheath (7), carbon nanotubes (diameter ≤ 20 nm) and polyvinyl chloride are mixed in a mass ratio of 1:10, and nano-sized tin dioxide particles with a particle size of ≤ 30 nm are added at a mass ratio of 0.2% to 0.5%. The composite material is treated by ultrasonic-assisted microwave radiation technology, wherein the ultrasonic power is 300 to 500 W and the treatment time is 10 to 20 minutes; the microwave radiation power is 500 to 1000 W and the radiation time is 5 to 10 minutes. During the treatment process, the dispersion of the carbon nanotubes and the nano-tin dioxide particles in the polyvinyl chloride matrix is enhanced by the ultrasonic-assisted technology, and the microwave radiation technology is used to promote the uniform mixing of the composite material and the optimization of the physical properties.
10. A method for preparing a fire-resistant low-voltage wire and cable according to claim 2, characterized in that: In step S06, during the preparation of the shielding layer (6), a layer of nano-scale conductive coating is formed on the surface of the shielding layer (6) by plasma enhanced chemical vapor deposition (PECVD) technology; the coating is composed of nano silver particles and graphene composite materials, and is deposited under low temperature conditions by plasma enhanced technology, with a thickness of 50-100 nm; the electromagnetic shielding performance of the shielding layer (6) is improved, and its corrosion resistance and wear resistance are enhanced; the specific process steps are as follows: Preparation of coating material: Nano-silver particles with a particle size of ≤50 nm and graphene with an interlayer spacing of ≤0.4 nm are mixed in a mass ratio of 1:2 to form a composite material; Plasma enhanced deposition: PECVD technology is used on the surface of the shielding layer (6) to excite the deposition gas (containing silver precursor and graphene dispersion) through radio frequency plasma (frequency 13.56 MHz) and deposit at a low temperature of 200-300°C; Deposition parameter control: deposition time is 30-60 minutes, deposition pressure is 0.1-0.5Pa, and deposition power is 50-100W to ensure uniformity and adhesion of the coating; Coating performance optimization: By adjusting the ratio of nanosilver particles and graphene, as well as deposition parameters, the electromagnetic shielding effectiveness (EMISE) of the coating can reach 40-50dB in the X-band (8.2-12.4GHz).
Citation Information
Patent Citations
Fire-resistant building wire and cable and preparation method thereof
CN118737555A
Insulating wire having excellent partial discharge resistance and high partial discharge inception voltage
CN103971797A
Method for improving adhesive power of ink in plastic prints
CN106397815A
Heat-conducting product with layered fold structure
CN108531143A
Boron nitride coating as well as preparation method and product thereof
CN112921298A